ChemInform Abstract: Enantioselective Ruthenium‐Catalyzed 1, 3‐Dipolar Cycloadditions Between C‐Carboalkoxy Ketonitrones and Methacrolein: Solvent Effect on Reaction Selectivity and Its Rational. Issue 41 (7th October 2014) - Selim, Khalid B.; Martel, Arnaud; Laurent, Mathieu Y.; Lhoste, Jerome; Py, Sandrine; Dujardin, Gilles
Abstract In the presence of the Ru catalyst (RUC), ketonitrones of type (I) are found to react with methacrolein with high regio‐, diastereo‐, and enantioselectivity.